ASAS LEGALITAS DALAM PERSPEKTIF FILSAFAT HUKUM - Vincentius Patria Setyawan (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
This article discusses legal issues related to the history and process of the formation of the principle of legality which is a fundamental principle in criminal law in various countries, including Indonesia. Tracing the history and development of the principle of legality shows that the principle of legality is much influenced by the thoughts of philosophers from various countries. The purpose of the principle of legality is to provide guarantees and protection of human rights for citizens from the arbitrariness of the authorities in applying the provisions of criminal law. This research is a normative legal research using a conceptual approach that is grounded in theories / doctrines of legal experts used to answer legal issues / issues in this article. The analysis technique used in the writing of this article is a deductive analysis technique, and uses legal material collection techniques in the form of library research (library research) and internet search (cyber-research). The results of this study are a common thread among philosophers' thoughts which form the basis of the formation of the principle of legality, including in Indonesia which is still valid today in Article 1 paragraph (1) of the Criminal Code.